A behavioural approach to foreign-market expansion to turbulent markets: a case of the internationalisation of seven Finnish corporations to the Republic of South Africa. (23rd February 2007) - Habiyakare, Evariste; Tornroos, Jan-Ake
In this paper, the power of behavioural and location-based approaches are used as a framework in studying how Finnish MNCs have entered and developed their presence in the South African market. The behavioural approach provides for an understanding of the foreign-market expansion process to this turbulent market, especially concerning process industries. The foreign-market expansion process to the developing and emergent market is, however, largely dependent on the local institutional changes and the existing network of actors in that context. Trying to understand the core process involved in foreign-market entry and expansion to turbulent markets of Africa requires a multifactorial analysis. Here the following factors are proposed: the reasons (the R-factor), the environment (the E-factor) the modal choice (M-factor), the network (N-factor), the events (Ev-factor) and finally the Time (T-factor) (REMNET). The authors propose a cross-fertilisation of these key elements in developing a behavioural approach with a locational approach for corporate internationalisation. Through empirical cases it will be shown how Finnish firms have been exploiting new opportunities to strengthen their presence in this new market. The paper aims to increase understanding of the dynamics and behavioural–locational aspects of foreign-market expansion by analysing the foreign-market expansion process of Finnish multinationals to the Republic of South Africa.